A framework for SPMD applications with load balancing - Plastino, Alexandre; Ribeiro, Celso C.; Rodriguez, Noemi (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
This work describes SAMBA, a framework for the development of a parallel SPMD applications with load balancing. SAMBA contains the structure common to different SPMD applications and a library of load-balancing algorithms. This structure allows the developer to concentrate on the specific problem at hand. The load-balancing library make easier the identification of the mot appropriate strategy for a given application. Experiments conducted with SAMBA on threee different parallel applications are described, illustrating the ease of use of the proposed framework and the relevance of load balancing.